Kultur Teknis Padi Sawah Di Desa Bubulak, Kecamatan Bogor Barat, Kota Bogor, Jawa Barat - Chelvi Agnariosa; Prayoga Suryadarma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Bubulak village is an area where almost all of its land has been turned into housing, so there is less land for agriculture. However, there are some paddy fields whose size is only ± 300 m to ± 600 m. The problems that occurs is the existence of Plant Pests (PP). PP include pests, diseases and weeds that interfere with the physiology of plants, eat parts of plants, become intermediaries for other organisms that are more destructive, disturbing in obtaining living necessities of cultivated plants. Pests that often attack rice plants are brown planthopper (Nilaparvata lugens), sting bug (Leptocorica acuta), rats, and fleas. Avoiding the pest attack can be done with the right technical features such as spacing, rotation of varieties, and irrigation. This study aims to determine the technical culture carried out by Bubulak village farmers on lowland rice to eracdicate Plant Pests (PP). This study was conducted in Bubulak village, West Bogor District, Bogor City. The method used is an interview to the community. The results obtained are rice varieties plants by farmer is IR 64. The spasing system used is not jajar legowo system and makes the irrigation system around the plantations. It can be concluded that the technical culture (method of cultivation of farmers in Bubulak village is still not appropriate in planting lowland rice. Key words: plant pests (PP), rice, technical culture